Sectıonal Arches In Begg Technıoue - Zahir Altuğ (Galenos Yayinevi, 1989)
The aim of this article is to imply that sectional arches which are frequently used in Edgewise technique whereas not in Begg Technique, can also be used in Begg technique. Sectional arches are mostly used in distalisation of canins. Besides, according to the tooth extarcted, e.g. premolars 1,2 it is also possible to retract the teeth by using sectional arches. In Begg technique, by means of elastics attached to helix on the mesial side of the canins, it is not possible to give the canins a unique movement, instead all of the anterior tooth from canin to canin are extracted. Therefore, this condition in this article, the feasibility of sectional arches in Begg technique has been discussed together with its advantaages.